Effectiveness of oral sildenafil for neonates with persistent pulmonary hypertension of newborn (PPHN): a prospective study in a tertiary care hospital. (12th December 2022) - Kamran, Amber; Rafiq, Nida; Khalid, Adeel; Amin, Fatima; Kumari, Veena; Shaikh, Abdul Sattar; Tebha, Sameer Saleem; Patel, Najma
Abstract: Introduction: The prevalence of persistent pulmonary hypertension of newborn (PPHN) has been estimated 1.9/1000 live births. Although the efficacy of inhaled nitric oxide and extracorporeal membrane oxygenation in PPHN is well established but it is difficult to administer and monitor in resource limited countries. Owing to this, other treatment options need to be evaluated. Method: This is a prospective observational study conducted in the Pediatric Cardiology Department, NICVD, Karachi, from February 2020 to October 2020 after the approval from the Institutional Ethical Review Committee. All the neonates referred to our Unit were screened by echocardiography (echo) and those who fulfilled the inclusion criteria were included. Echo were done before starting sildenafil and after 72 h to assess the pressure gradient across tricuspid valve and right to left or bidirectional shunt across patent ductus arteriosus, patent foramen ovale, or both. Sildenafil was started with a dose of 1 mg/kg/dose thrice a day and increased to 2 mg/kg/dose after 48 h if partial pressure of oxygen (PO1 ] did not increase. In neonates who did not respond to increased dose of Sildenafil were added on oral Bosentan 1 mg/kg/dose twice a day. Results: Total 82 newborns were enrolled. Fifty-two patients improved after 48 h so were continued on same treatment. Sildenafil dose was increased in 30 (37.9%) patients whose PO2 did not increase to at least 10% from baseline after 48 h of starting treatment. Three patients expired within 48–72 h. Out of 27 remaining patients, only four responded whereas 23 patients did not show any improvement. In these patients, Bosentan was supplemented along with sildenafil. Conclusion: The results of our study show effectiveness of oral Sildenafil in treating PPHN. The overall improvement observed in the patients was overwhelming. Combination of Sildenafil with Bosentan is beneficial in patients who did not respond on Sildenafil alone.